WORKING FROM HOME: KINERJA KARYAWAN BPJS KESEHATAN CABANG MEULABOH PADA ERA PANDEMI COVID-19 - Sinta Yulistia; Rusma Setiyana (Warmadewa Management and Business Journal (WMBJ), 2022)
This study aims to find out how the performance of BPJS Kesehatan Meulaboh employees and what obstacles are faced by BPJS Kesehatan Meulaboh employees during the covid-19 pandemic. This research was conducted in July – August 2021. The research population consisted of all employees who worked at the BPJS Kesehatan Meulaboh and only 10% of the total of employees were taken as the samples. This research was conducted using a qualitative descriptive analysis method by collecting data through interview techniques. The results of this study indicate that as many as 80% of employees claim that the work done with the WFH system is not effective, the time and place of work are less flexible (58%) and employees are also less focused and comfortable with the system (58%) in order that it affects employee performance productivity. Although there are several positive sides such as being able to save time and money, employees experience several obstacles during WFH, namely having limitations in communicating with superiors, colleagues, and the community directly so that it has an impact on misunderstandings and disputes, lack of facilities and supporting media, and sometimes having bad network.